2019
DOI: 10.1075/lab.18048.cab
|View full text |Cite
|
Sign up to set email alerts
|

Initial phonological transfer in L3 Brazilian Portuguese and Italian

Abstract: This study examines five variables posited to drive(s) initial phonological transfer of (part of) one system over another in an L3: language status (L1/L2), facilitation, global structural similarity, dominance, and bilingual experience. Specifically, we investigate production of intervocalic voiced stops by English/Spanish bilinguals at the initial stages of L3 Brazilian Portuguese (BP) or Italian. These segments surface as [−continuant] in BP, Italian, and English but are realized as [+continuant] in Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
1
8
0
1
Order By: Relevance
“…In L3 English, the HSs VOT productions did not differ from those of L1 English and the HSs outperformed the L1 Italian control group. In theory, these results pattern both with studies that have shown phonological CLI from the typologically closest language (e.g., Cabrelli & Pichan, 2021), and also with studies that argue for CLI from the dominant language (e.g., Gabriel et al, 2016; Llama & López-Morelos, 2016, 2020; Lloyd-Smith et al, 2017). However, it is debatable to what extent typological proximity (in the sense of genealogical relatedness) plays a role when languages have a different phonological make-up.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In L3 English, the HSs VOT productions did not differ from those of L1 English and the HSs outperformed the L1 Italian control group. In theory, these results pattern both with studies that have shown phonological CLI from the typologically closest language (e.g., Cabrelli & Pichan, 2021), and also with studies that argue for CLI from the dominant language (e.g., Gabriel et al, 2016; Llama & López-Morelos, 2016, 2020; Lloyd-Smith et al, 2017). However, it is debatable to what extent typological proximity (in the sense of genealogical relatedness) plays a role when languages have a different phonological make-up.…”
Section: Discussionsupporting
confidence: 76%
“…Although several L3 models have been proposed to account for morphosyntactic transfer (see, e.g., Puig-Mayenco et al, 2020, for an overview), we still know little about the processes that drive CLI in the phonological domain (see, e.g., Cabrelli & Pichan, 2021; Kopečková, 2016). This is even truer for HSs, who have so far only seldom been the focus of L3 phonology research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on phonological CLI in L3 acquisition does not show conclusive evidence for any of the models individually: while Williams and Hammarberg's (1998) and Hammarberg's (2001) case study of the phonology of an L1 English and L2 German speaker producing her first words in L3 Swedish seems to support the L2SF, Wrembel (2012) and Lloyd-Smith et al (2017) found partial confirmation of the TPM in their studies on foreign accentedness. Likewise, Cabrelli and Pichan (2021) found evidence for transfer driven by global structural similarity, at least in a language triad in which there is a clear similarity between the L3 and one of the source languages. In contrast, other studies have found some evidence consistent with the predictions of the CEM: Onishi (2016) on L3 phoneme perception, Sypiańska (2016) on L3 vowel production and Wrembel (2012) on foreign accent.…”
Section: Existing L3 Acquisition Modelsmentioning
confidence: 86%
“…There are a number of important issues to be considered with respect to the findings of these L3 phonology studies. For one, although L3 learners at early stages of acquisition were included in the studies, they did not always represent the very initial stage of L3 acquisition, having been exposed to the L3 for a couple of months rather than hours (but see Cabrelli and Pichan, 2021). Likewise, they mostly analysed the acquisition of a single structure rather than compared across several structures, which precludes an adequate testing of models such as the LPM or the SM (for a notable exception, see Domene Moreno, 2021).…”
Section: Existing L3 Acquisition Modelsmentioning
confidence: 99%